1-D numerical modelling in limestone precipitate for selfhealing concrete using finite element method (FEM) - Ahmad Asyraf Jamalludin, 1996-, author; Halinawati Hirol, 1977-, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Muda Kejuruteraan (Awam))- Universiti Teknologi Malaysia, 2019